(untitled) (Cambridge, Mass., 1989)
This book considers instead assumptions and analyses that reconcile theory with the realty of successful state intervention. Proposed here í a new analytical framework for understanding Japan's devel.
Keywords: Industrial productivity,Industrial policy,Năng suất công nghiệp,Chính sách công nghiệp; Japan,Japan,Nhật Bản,Nhật Bản